Network study of miRNA regulating traumatic heterotopic ossification - Kun Lian; Zhiyan Chen; Leijie Chen; Yongmei Li; Luping Liu (PLoS ONE, 2025)
Objective Objective: To identify and analyze the microRNAs that are expressed differently (DE-miRNAs) and forecast their potential roles in the pathophysiological process of traumatic heterotopic ossification (THO). Methods We conducted RNA sequencing on six samples of normal bone and THO tissues from the patients and conducted differential expression analysis of miRNA. The biological activities of the target genes of the differentially expressed microRNAs (DE-miRNAs) were investigated using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses. The miRNA-mRNA network was constructed using Cytoscape software, incorporating miRNAs with varying expression levels and their corresponding target genes. Results In comparison to the normal control group, a total of 84 differentially expressed microRNAs (p<0.05, |log2FC|>1) were identified, with 27 microRNAs showing up-regulation and 57 microRNAs showing down-regulation. The functional enrichment analysis revealed that the target genes of the de-mirna were primarily enriched in biological processes such as the regulation of protein stability and the management of neuromuscular process balance. Additionally, a miRNA-mRNA expression regulatory network was established. The RT-qPCR analysis revealed that miR-142-3p, miR-150-5p, miR-421, miR-625-5p, miR-675-5p, and miR-940 exhibited a decrease in expression levels in THO tissues. Nevertheless, the expression levels of miR-181c-3p, miR-320c, miR-497-5p, and miR-99a-5p were increased in THO tissues. Conclusions Our investigation has uncovered the expression patterns and projected the potential activities of differentially expressed microRNAs (DE-miRNAs) in human THO. This research may contribute to a better understanding of the underlying mechanisms and offer new possibilities for therapeutic targets in THO.